REFORMING OF THE HOUSING AND COMMUNAL SPHERE IN URBAN AGGLOMERATIONS UNDER DECENTRALISATION CONDITIONS (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The article considers theoretical and practical problems of development of housing and communal sphere of urban agglomerations in the conditions of decentralisation. The essence and meaning of the concept of "decentralisation" are detailed, the interpretation of scientific publications on this issue is concretedly. The stages and peculiarities of the formation of urban agglomerations of housing and communal services in the regions of Ukraine are investigated. The main features and types of the prevailing urban agglomerations in Ukraine, as well as the main obstacles which prevent their successful implementation into the economic structure of the region are described; The specifics of creating urban agglomerations leading countries of the world are noted. An effective normative-legal provision of the effectiveness of urban agglomeration is analyzed. The of substantiated that the experience of reforming the housing and communal sector of each country is unique and reflects the specifics of a particular state, which leads to the inefficiency of the introduction of foreign experience, without taking into account its own economic, Social and territorial potential. The agglomeration effect, obtained by the effect from the scale, an increase of the relative rate of services rendered per unit area, quantitative and qualitative growth of servicing due to the efficiency of research institutions, educational and actions of the social infrastructure. Priority directions of penetration of innovative approaches and methods in housing-communal sphere of urban agglomerative regional grouping are formed. It is proved that dynamism of the processes of reforming of the housing and communal sphere of urban agglomerations depends on efficiency of public-private capital mechanisms for realization of important infrastructure objects.Тhe purpose of the articl. The substantiation of the reform approaches to the development of urban agglomerations in the conditions of decentralisation by forming the agglomeration effect at enterprises for population livelihoods.Results. In this aspect, it is important to obtain the state financial support of the introduction of innovative mechanisms and facilitate the modernization of the city engineering infrastructure based on modern technological solutions. Continuation of the process of financing reforms in terms of decentralization and energy efficiency is still a budget priority for the year 2020. However, given the chronic deficit of the state budget, the issues of the innovation and investment source of infrastructure objects leads to the search for extra-budgetary cells, among which the key place is given to international financial organizations.Conclusiоns. Therefore, due to the agglomeration effect on housing and communal economy the important role is given to measures specialized research institutions that function in the comprehensive economic and legal analysis and sociological research features Functioning of the individual local agglomeration, as well as monitoring the State and development trends of housing and communal services including the effectiveness of public-private capital mechanisms for the implementation of important infrastructure facilities.
Keywords: Urban agglomeration, housing and communal sphere, decentralization, infrastructure, communication, investment capital, energy efficiency